Acute hemorrhagic edema of infancy: a self-resolving condition with scary presentation. - Konda, D. (European Journal of Pediatric Dermatology, 2023)
Acute hemorrhagic edema of infancy (AHEI) also known as Finkelstein’s disease or Seidlmayer’s cockade purpura is a benign, self-limiting cutaneous leukocytoclastic vasculitis. AHEI begins suddenly with a striking clinical picture, but usually resolves on its own within 1 to 3 weeks. Therefore, a high index of suspicion and an early diagnosis of this condition are essential to avoid unnecessary investigations and therapies. We report a case of a 9-month-old girl who presented with ecchymotic plaques on her lower extremities and ears, diagnosed as Finkelstein’s disease and then managed conservatively.